INTERNET NETWORK CLASSIFICATION IN MALIKUSSALEH UNIVERSITY USING NAÏVE BAYES METHOD - Eva Darnila; Zara Yunizar; Dhyra Gibran Alinda (Universitas Methodist Indonesia, 2021)
The utilize of web systems at this time is exceptionally critical, particularly for the world of instruction. In expansion to the significance of the web arrange, issues frequently emerge on the web arrange due to an expansive number of clients, the issues can be gotten at the UNIMAL campus incorporate moderate, harmed, and indeed not sent information to its goal since the organize activity isn't ideal. To be able to optimize the web organize by prioritizing organize activity. In this consider, the Credulous Bayes calculation is utilized for the classification handle of organize activity capture information. The application utilized to capture organize activity is the Wireshark application. Utilizing the Credulous Bayes calculation to watch the comes about of organize test information through a calculation prepare that has tall precision. To be specific at the Workforce of Designing 95.73% with a likelihood of testing comes about is 0.00015946 web browsing, 0.00000007 downloads, 0.00008691 gushing, 0.00008497 social media, 0.00000014 floodings.